Frugivorous flies (Diptera: Tephritidae and Lonchaeidae) in the Mundaú Valley in the state of Alagoas, Brazil - Batista, Natanael Silva; dos Santos, Jakeline Maria; Forti Broglio, Sônia Maria; Santos, José Rosildo Tenório dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
This study aims to know the diversity and the fruit flies infestation rates in the Mundaú valley in the state of Alagoas. The fruits were collected randomly every two weeks at different times of the crown of fruit and freshly fallen fruit on the ground, which were in good condition of conservation and without exit holes of the larvae. The fruits were placed in plastic trays (54cm x 32cm) labeled with field data having a layer of a cm sieved sand and sterilized in an oven with air circulation for 48 hours at 80 ° C to serve as a substrate for pupation . The infestation indices of fruit flies were calculated by dividing the total number of pupae by total fruit each collected species (pupae / fruit) and total number of pupae by the total weight (kg) of each collected species (pupae / kg fruit). Were identified five fruit flies species: Anastrepha fraterculus (Wiedemann, 1930), Anastrepha obliqua (Maquart, 1835), Anastrepha sororcula Zucchi, 1979, Anastrepha zenildae Zucchi, 1939 e Ceratitis capitata (Wiedemann, 1824) (Diptera: Tephritidae) and Neosilba species (Diptera: Lonchaeidae). Yellow mombin, guava, surinam cherry and red mombin are the fruits that suffer the greatest infestation of fruit flies. The most polyphagous species in this study is A. fraterculus.